Coca chewing and the botanical origins of coca (Erythroxylum SSPP.) in South America - Plowman, Timothy (1985)
Coca and Cocaine: effects on people and policy in Latin America / Pacini, Deborah - ed. -- Cambridge : Cultural Survival / LASP, 1985 . -- 170 p